Assessment of non-grain parameters in wheat quality under - MOHAN, DEVINDER MOHAN; Gupta, Raj Kumar (Journal of Cereal Research, 2025)
Influence of crop seasons, sites and their interactions was examined to compare wheat grain quality in two important and agro-climatically diverse wheat zones of India i.e. north western plains zone (NWPZ) and central zone (CZ). Six leading cultivars of each zone were evaluated for eleven important parameters at five locations during four year study period. Locations made big difference in congenial environments of NWPZ but under hot and dry environments of CZ, chapati quality and sedimentation value remained unaffected. Crop season variations made no difference in chapati and grain appearance scores of NWPZ whereas test weight and grain hardness registered no impact in CZ. Variations imposed by sites and years were of the same magnitude in NWPZ but not in CZ. Under hot climate, seasonal variations superseded site differences for traits like chapati quality score, biscuit spread factor and sedimentation volume. In contrast, site differences assumed greater relevance than crop seasons in test weight and gluten content under such climates. Site-year interactions assumed significance in majority of the cases but such variations could not exceed variations in sites or crop seasons. Chapati quality in CZ was not affected by site-year variations. Biscuit quality, protein and gluten contents registered very strong influence of sites, crop seasons and their interactions. Site-variety interactions were inconsequential in both regions. Year-variety interactions also remained non-significant in majority of the traits in both zones except for chapati and bread quality scores in central India. Variations caused by genotype-environment interactions proved insignificant in quality of Indian cultivars but year-site interactions assumed significance although its impact was very small in comparison to site or crop seasons. Character response to sites and crop seasons was examined under different climatic conditions.